2004
DOI: 10.1016/s0378-1097(03)00896-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various culture environments on expression of major outer membrane proteins fromPorphyromonas gingivalis

Abstract: We examined the effects of various culture environments on major outer membrane proteins from Porphyromonas gingivalis ATCC 33277. Major outer membrane protein patterns on gel electrophoresis showed little difference over the culturable range of osmolarity and pH. With elevated temperature or prolonged culture, the intensities of the gingipain bands decreased; however, bands of RagA, RagB and the putative porins were relatively stable. Similar results were observed with several different culture media. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 47 publications
(58 reference statements)
2
32
0
Order By: Relevance
“…In the absence of a specific antibody to Rag4, it was not possible to confirm the identity of this protein. However, Murakami et al recently determined by N-terminal sequencing that both RagA and a variant of RagB that can now be confirmed to be RagB4 are expressed in ATCC 33277 T (rag-4), where they represent two of the seven major outer membrane proteins (22,23). Sequence comparisons of the four rag alleles.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of a specific antibody to Rag4, it was not possible to confirm the identity of this protein. However, Murakami et al recently determined by N-terminal sequencing that both RagA and a variant of RagB that can now be confirmed to be RagB4 are expressed in ATCC 33277 T (rag-4), where they represent two of the seven major outer membrane proteins (22,23). Sequence comparisons of the four rag alleles.…”
Section: Resultsmentioning
confidence: 99%
“…It was noteworthy that only trace amounts of RagA, RagB, and OmpA-like proteins existed in the supernatant fraction. The above-mentioned major protein identification, based on mobility in SDS-PAGE, was carried out previously (41)(42)(43).…”
Section: Resultsmentioning
confidence: 99%
“…P. gingivalis expresses two types of fimbriae, long fimbriae composed of FimA (fimbrilin) (67), and short fimbriae composed of a 75-kDa protein (21, 51, 68). Many studies have shown that FimA has various functions, which include attachment to and invasion of gingival epithelial cells (28, 64), coaggregation with other species of bacteria (2), attachment to salivary components (4), activation of fibroblasts and macrophages (24), induction of inflammatory cytokines, and bone resorption (23).Several proteins are often found in the outer membrane fraction, particularly RagA, RagB, Arg-gingipains (Rgps), Lysgingipain (Kgp), and the OmpA-like proteins (41,42). RagA is a TonB-dependent outer membrane receptor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Pgm6/7 protein heterotrimers were partially digested with Staphylococcus aureus V8 protease to analyze the internal sequences as described previously (28). Heterotrimers and homotrimers were also analyzed by matrix-assisted laser-desorption ionization-time-of-flight mass spectrometry (MS).…”
mentioning
confidence: 99%